2018
DOI: 10.1590/1806-9282.64.12.1117
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of liquid or foam sclerotherapy in small varicose veins (ceap c1) with venous clinical severity score

Abstract: SUMMARY OBJECTIVE: We aimed to evaluate the efficacy of liquid or foam sclerotherapy of varicose veins using venous clinical severity scores and possible complications. METHODS: A total of 318 patients (268 females, 50 males) who were treated with liquid or foam sclerotherapy between January 2012 and December 2012 were included in this study. RESULTS: Skin necrosis was observed in only 6 patients (1. 8%), thrombophlebitis in 10 patients (3. 1%), and hyperpigmentation in 18 patients (5. 6%) in this study gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Darvall and colleagues analyzed the expectations of 351 patients who underwent foam sclerotherapy for lower extremity venous insufficiency, and they concluded that up to 25% of patient expectations were not met [ 13 ]. Also, Kaygin and Halici stated that foam sclerotherapy was a more painful procedure compared to liquid sclerotherapy; however, the difference was not statically significant [ 6 ]. In contrast, Moser et al used foam sclerotherapy and liquid sclerotherapy for hemorrhoidal disease and found that patient satisfaction was significantly higher with foam sclerotherapy [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Darvall and colleagues analyzed the expectations of 351 patients who underwent foam sclerotherapy for lower extremity venous insufficiency, and they concluded that up to 25% of patient expectations were not met [ 13 ]. Also, Kaygin and Halici stated that foam sclerotherapy was a more painful procedure compared to liquid sclerotherapy; however, the difference was not statically significant [ 6 ]. In contrast, Moser et al used foam sclerotherapy and liquid sclerotherapy for hemorrhoidal disease and found that patient satisfaction was significantly higher with foam sclerotherapy [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies investigated the efficiency and safety of different medical agents for the management of reticular varicose veins and telangiectasia of the lower extremity, and the efficiency of liquid sclerotherapy and foam sclerotherapy was proven. Kaygin and Halici applied foam and liquid sclerotherapy in patients with lower extremity varicose veins, and the authors stated that both foam and liquid sclerotherapy were safe treatment options with acceptable complications [ 6 ]. In another study, Hamahata et al achieved higher success with foam sclerotherapy in patients with lower extremity varicose veins [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…This method has highest chances of recurrence compared to other surgical modalities like stripping, endovenous laser ablation, and radiofrequency ablation [20, 22]. Other notable side effects in UGFS are pigmentation, painful thrombosed veins, allergy to drug [23, 24].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the immediate complications after foam sclerotherapy for varicose veins are extravasation, pain, visual disturbance, and chest pain while delayed complications include pigmentation, painful thrombosed veins and deep vein thrombosis [30]. In another study, hyperpigmentation was seen in 5.6%, painful thrombosed veins in 3.1% and skin necrosis in 1.8% of cases post sclerotherapy for varicose veins [24].…”
Section: Discussionmentioning
confidence: 99%
“…One trial measuring VCSS scores at 1 month postoperatively demonstrated significantly decreased pain in both liquid and foam sclerotherapy, with no statistically significant difference between modalities [ 222 ]. Pain was also reduced at 15 days and 30 days postoperatively in two other controlled trials, although this difference was not statistically significant at 90 days [ 223 , 224 ].…”
Section: Advances In Minimally Invasive Treatmentmentioning
confidence: 99%